Evolving Eldercare in Contemporary China Two Generations, One Decision - Chen, Lin.; SpringerLink (Online service) (New York : Palgrave Macmillan US (Imprint), 2016)
With an increasing number of elders moving into nursing homes, the shift from family to nursing home care calls for an exploration of caregiving decision-making in urban China. This study examines how a rapidly growing aging population, the one-child policy, and economic reform in urban China pose unprecedented challenges to the country's ingrained tradition of family caregiving. It presents interviews of matched elders and their children from a government-sponsored nursing home in Shanghai and analyzes the decision-making process of institutionalization. This book offers fresh insight into the evolving culture and arrangements of caregiving in contemporary Chinese society, illuminating the diverse needs for long-term care of Chinese elders-the world's largest aging population-in the coming decades.
Keywords: Welfare state; Sociology of Family, Youth and Aging